2018
DOI: 10.1177/1742395318759587
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Pittsburgh Sleep Quality Index subscales and diabetes control

Abstract: Objectives Data suggest that poor sleep quality as measured by the Pittsburgh Sleep Quality Index (PSQI) contributes to suboptimal diabetes control. How the subscales comprising the PSQI individually relate to diabetes control is poorly understood. Methods In order to explore how PSQI subscales relate to diabetes control, we analyzed baseline data from a trial of a telemedicine intervention for diabetes. We used multivariable modeling to examine: (1) the relationship between the global PSQI and hemoglobin A1c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…The Pittsburgh Sleep Quality Index (PSQI) was originally developed in 1989 to measure sleep quality for psychiatric research as well as clinical practice [22]. The index has since been used to assess sleep quality in patients suffering from T1DM [18] as well as T2DM [23]. An Arabic version has been developed and tested in a nonclinical setting [24] as well as in patients with coronary artery disease [25].…”
Section: Introductionmentioning
confidence: 99%
“…The Pittsburgh Sleep Quality Index (PSQI) was originally developed in 1989 to measure sleep quality for psychiatric research as well as clinical practice [22]. The index has since been used to assess sleep quality in patients suffering from T1DM [18] as well as T2DM [23]. An Arabic version has been developed and tested in a nonclinical setting [24] as well as in patients with coronary artery disease [25].…”
Section: Introductionmentioning
confidence: 99%
“…At present, many experimental and epidemiological studies have reported that poor sleep quantity and quality are related to the greater prevalence of high-fasting plasma glucose and high A1c level. [ 1 2 3 4 ] Most recently, systematic and meta analyses have reported that difficulties in both short and long durations of sleep are associated with the severity of diabetes. [ 5 ] Many studies provided evidence that sleep quality influences the glycemic control among type 2 diabetes mellitus (T2DM) patients and approximately 37%–50% of T2DM patients have sleep problems, which is higher than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, study and data suggest that poor sleep quality as measured by the PSQI contributes to suboptimal diabetes control. [12] Sleep disturbances have effect and increase HbA1c level. In fact, the mechanism for the relationship between sleep disturbances and HbA1c was presented very clearly in the current study and it is consistent with previously reported studies.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many experimental and epidemiological studies have reported that poor sleep quantity and quality are related to greater prevalence of high fasting plasma glucose and high HbA1c level. [11121314] Most recently, studies have been reported that long durations of sleep are associated with severity of diabetes. [15161718] Many studies provided evidence that sleep quality influences the glycemic control among patients with type 2 diabetes mellitus (T2DM) and approximately 37%–50% of patients with T2DM have sleep problems, which is higher than the general population.…”
Section: Introductionmentioning
confidence: 99%